FABLES IN THE LITERARY HERITAGE OF BARASBI TKHAMOKOV: POETICS AND PROBLEMS - K. O. KHASHIR (Кавказология, 2021)
The article examines the fable heritage of the Kabardian writer Barasbi Tkhamokov. The relevance of the study is associated with the absence of scientific works in Adyghe (Circassian) literary criticism, devoted not only to fables, but in general to the literary work of B. Tkhamokov, and for the first time the author of the article made an artistic translation of fables into Russian. Fables from the poetry collection of the writer «Quiet Word» namely «The Frog and the Snake» («Хьэндыркъуакъуэмрэ Благъуэмрэ»), «Barbarea and Grass» («Хьэкъыршымрэ Шыдудзымрэ»), «Dugout and a spring» («ЩIыунэмрэ Псынэмрэ»), «Duck head» («Бабыщыщхьэ»), «Wasp and bees» («Хьэдзыгъуанэмрэ Бжьэхэмрэ»), «Insect and cabbage» («ХьэпIацIэмрэ Къэбыстэмрэ»), «Bear and Wolf» («Мыщэмрэ Дыгъужьымрэ»), «Respect and Happiness» («Нэмысымрэ Насыпымрэ») are in the center of research attention. B. Tkhamokov's ideological views, his philosophical understanding of life and reliance on the Circassian code of ethics «Adyge khabze» are traced in the designated works. The study used the method of literary analysis. The results obtained can be used in the preparation of special courses on the Circassian literature.